Sexual dichromatism in a Mexican checkered beetle (Coleoptera: Cleridae: Neorthopleurinae) - Rifkind, Jacques (Zootaxa, 2013)
This paper describes sexual dichromatism in the Mexican checkered beetle Nelsonoplium jeanae Barr, an unusual case for the Cleridae. Although sexual dimorphism is common in Cleridae, it is primarily expressed in morphological differences such as antennal composition, relative body size, shape of the hind legs, and the structure of the terminalia. Polychromatism is often encountered in clerids, with different color phena sometimes occurring within the same population. For example, Colyphus signaticollis Spinola presents in various concolorous, banded and striped elytral forms (Ekis 1977), and I have beaten several distinct morphs of this species (or near) from oak at the same location in Sonora, México. Solervicens (personal communication) has observed non sex–linked dichromatism among species of Eurymetopum Blanchard and within Pelonium Spinola. Much confusion has been attached historically to the identity of many species of the epiphloeine genus Ichnea Castelnau because earlier workers counted primarily on coloration to diagnose taxa. Recognizing the plasticity of elytral color pattern within the genus, and its unreliability for species determination, Opitz (2010) synonymized no fewer than 17 of the 31 previously described species. Solervicens’ (1986) study of Eurymetopum revealed that certain color morphs occur more frequently within one sex than the other, and he discusses a species within which the typical color pattern is expressed in males and some females while other females have their own distinct coloration, not found among males. Nevertheless, records of consistent sexual dichromatism in clerids are rare. Gerstmeier (2013) reports and illustrates a pair of an Indonesian Tenerus sp. where the male and female are so different in habitus and coloration from one another that they could easily have been mistaken for separate species had they not been collected in copula. As far as I am aware, the present note represents the first record of a North or Central American clerid exhibiting a similar dichromatism.